Analisis Pengendalian Kualitas Menggunakan Metode Seven Tools dan Perbaikan Proses dengan Pendekatan PDCA - Saputra, Fahmi Dwi; Nugroho, Dony Satriyo (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze and enhance the quality of the pipe sales process by implementing the Seven Quality Control (QC) Tools combined with the Plan, Do, Check, Action (PDCA) approach. The research was motivated by a high defect rate and frequent customer complaints that negatively affected service quality and sales performance. A descriptive quantitative method was applied, using data collected from observations, interviews, and one-year sales reports. The analysis utilized seven quality control instruments: check sheet, histogram, Pareto chart, cause-and-effect (fishbone) diagram, scatter diagram, control chart, and flowchart to identify the root causes of product defects. The results revealed that the most common defects were bent pipes, uneven diameters, and cracks during cutting, which were primarily caused by human factors, work methods, and material quality. The PDCA cycle implementation effectively reduced defect levels, improved compliance with standard procedures, and promoted a culture of continuous improvement. Consequently, the integration of Seven QC Tools and the PDCA cycle has proven effective in improving product quality, operational efficiency, and customer satisfaction sustainably.